(The Impact of Functional Information System on Competitive Advantage (An Applied Study on Omdurman National Bank- Sudan - Al Taher, Ibrahim Ahmed; Al Bashir, Abtahal Mohammed Ahmed (Journal of Economic, Administrative and Legal Sciences, 2019)
This study aimed to clarify the impact of the functional information and systems in the information systems in Omdurman National Bank (ONB) namely (production of banking services, marketing information systems, human resources information systems, financial and accounting information systems). The study adopted several methods such as historical, descriptive, conductive and analytical methods. Obtained results concluded that both information systems for the banking production services and marketing information systems have an impact on achieving competitive advantage, in addition to that both financial and accounting information systems and human resources information systems have no effect on the competitive advantage of Omdurman National Bank.